2021
DOI: 10.3390/foods10020306
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Lockdown and Self-Perceived Changes of Food Choice, Waste, Impulse Buying and Their Determinants in Italy: QuarantEat, a Cross-Sectional Study

Abstract: Data about self-perceived food choice (FC) changes and their determinants during COVID-19 lockdowns are limited. This study investigated how the Italian lockdown affected self-perceived food purchases (FP), occurrence of impulse buying (IB), household food waste production (HFWP) and their determinants. A web-based cross-sectional survey was distributed in May 2020, collecting an opportunistic sample of the Italian population. A total of 1865 (70% females) people were enrolled, the median age was 29 (IQR 16.0)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 34 publications
1
75
1
1
Order By: Relevance
“…Some of the studies report improvements and others report worsening diets. In Italy, the lockdown highly affected food choice behaviours, leading to positive and sustainable purchase and consumption habits [ 13 , 36 ]. In the PLACE-19 study, in Polish adolescents, the authors concluded that the COVID-19 pandemic may have changed the food choice determinants, increasing the importance of health and weight control while reducing the role of mood and sensory appeal [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the studies report improvements and others report worsening diets. In Italy, the lockdown highly affected food choice behaviours, leading to positive and sustainable purchase and consumption habits [ 13 , 36 ]. In the PLACE-19 study, in Polish adolescents, the authors concluded that the COVID-19 pandemic may have changed the food choice determinants, increasing the importance of health and weight control while reducing the role of mood and sensory appeal [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of them observed an increase in the consumption of healthy foods and in home cooking practices, and a lower consumption of foods of poor nutritional value [ 7 , 9 ], while others found that, during lockdown, diet was characterized by a higher energy intake and lower nutritional quality than in 2019 [ 10 ]. Changes in eating habits were also observed in other European countries, such as Italy [ 11 , 12 , 13 ], Poland [ 14 , 15 ], Denmark [ 16 ], Germany, Slovenia [ 8 ], Ireland and Great Britain [ 17 ]. Although the reasons for these changes are still not fully understood, some authors have suggested that personal characteristics may modulate them, shaping different patterns of change [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 89%
“…As a consequence of the pandemic, the volume and sources of waste generation change; however, the traditional causes of environmental pollution from the different sectors like transportation, aviation, and industries have declined sharply (Myllyvirta 2020 ; Sarkodie and Owusu 2020 ). Similarly, the food production and consumption system has undergone significant changes and ultimately resulted in the sudden and radical change in the daily life of people worldwide and resulted in adverse effects on lifestyle, eating habits, and other household characteristics (Cosgrove et al 2021 ; Di Renzo et al 2020 ; Principato et al 2020 ; Scacchi et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for the decrease in waste were changes in eating and cooking habits, having more time to prepare and cook meals, and financial constraints. Also, the food waste amount has been associated increased food stock, increased in the amount of food purchased, and the amount of food cooked.In another study conducted in Italy, it was concluded that more than half of the participants (53.7%) reduced food waste in their households (Scacchi et al, 2021). In a study that included participants from the U.S. and Italy, approximately half (49.0%) of respondents reported a decrease in food waste during the Covid-19 pandemic than before the pandemic (Rodgers et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…The Covid-19 outbreak has caused changes in the characteristics of the food consumers to buy. Scacchi et al (2021) has found a decrease in the purchase of fresh products that can deteriorate quickly, characterized by short shelf life. Our study determined that 34.3% of the participants had a change in the characteristics of the foods they purchased.…”
Section: Discussionmentioning
confidence: 99%